Pengaruh Penerapan Model Pembelajaran Read, Answer, Discuss, Explain and Create (RADEC) Terhadap Literasi Sains Peserta Didik Kelas VIII - Idrus, Nur Istiqomah A.; Lestari, Tuti; Azzahra, Firda; Oktavia, Rani (Indo-MathEdu Intellectuals Journal, 2025)
The results of the Programme for International Student Assessment (PISA) show that the science literacy of students in Indonesia is still below the international average. A similar condition is also seen in the results of the Computer-Based National Assessment (ANBK) for eighth-grade students, which shows that science literacy skills have not been measured comprehensively. This study aims to determine the effect of the Read, Answer, Discuss, Explain, and Create (RADEC) learning model on the science literacy competence of eighth-grade students. This study is a quantitative study using a quasi-experimental method with a nonequivalent control group design. The research sample was determined using purposive sampling, involving one experimental class and one control class. The research instrument consisted of a 22-item multiple-choice science literacy test. Both groups were given pre-tests and post-tests to measure improvements in science literacy competence. The data were analyzed descriptively and quantitatively, with the results showing that Ha was accepted and H₀ was rejected. The t-test value showed that tcount 3.47 ≥ ttable 2.00, which was reinforced by the N-gain test results. These findings indicate a significant difference between the two groups, so it can be concluded that the application of the RADEC model has a positive effect on improving students' science literacy competency.